Analyzing Impact Hyperreality Blackpink The Game in Metaverse World of The Game Players - Dwikartini, Fanny; Saidi, Acep Iwan; Siregar, Harifa Ali Albar (Universitas Medan Area, 2025)
The increasing K-pop music industry phenomenon happens because of the influence of social media, which people quickly access. The simplicity of social media allows collaboration in the K-pop music industry. It can be seen from the partnership of a game developer with a Korean music agency to make a game named Blackpink The Game. By inviting players, players will be asked to simulate being a girl band producer so that the girl band becomes famous and builds a simulacra. Moreover, the players will be invited to be stimulated to be anoBlackpink members to complete a specific mission. With the hyperreality analytics of Baudrillard, simulacra in the Game chooses one member of Blackpink and finishes the task. At the same time, hyperreality is the interaction between members of Blackpink and the producer until there are no boundaries between reality and the virtual world. The study method is a literature review with Jean Baudrillard's theory of the reality of The Game players. The purpose of the study is to see the impact of hyperreality on Blackpink. The Game Players